Does digitalising the supply chain contribute to its resilience?. Issue 2 (10th November 2020) - Zouari, Dorsaf; Ruel, Salomée; Viale, Laurence
Abstract : Purpose: Supply chain resilience (SCR) is a key concept for managers who wish to develop the capacity to enhance their supply chain's (SC's) ability to cope with unexpected turbulence. SC digital tools are often seen as a solution that provides more visibility, anticipation and collaboration (SCR capability factors). The purpose of this paper is to investigate the link between SCR and SC digitalisation Design/methodology/approach: A sample was considered with 300 managers in the field of SCM, and the results were analysed using factor analysis and structural equation modelling (SEM). SEM was employed to test the impact of the degree of digital maturity and SC digital tools on SCR. Findings: SC digitalization is characterised by the degree of digital maturity and the adoption of SC digital tools. The degree of digital maturity has a strong influence on digital tool adoption. SCR is positively impacted by both the degree of digital maturity and the adoption of digital tools. Research limitations/implications: The findings do not indicate which tools contribute the most to SCR. Practical implications: Managers should reflect on the need to continue digitalizing their SCs if they want greater SCR in the current uncertain environment. Originality/value: This is the first quantitative study that focuses on assessing the impact of the degree of digital maturity and the SC digital tools adopted on SCR. Validation of the hypotheses model confirms the positive impact of SC digitalisation on SCR for researchers and managers.